Harmonisasi Hukum Pidana dan Kearifan Lokal dalam Penanggulangan Kebakaran Hutan dan Lahan di Kalimantan Barat - Ramadhan, Adam; Rahman, Adi Nur (Jurnal Ilmiah Penegakan Hukum, 2025)
This study analyzes the effectiveness of the implementation of positive criminal law and the challenges of legal harmonization in addressing forest and land fires (karhutla) in West Kalimantan, as well as formulates a harmonization model based on legal pluralism. The research employs a qualitative approach with interactive analysis through interviews with six regional officials and a review of legal documents. This model is expected to promote a more inclusive and sustainable legal approach and enrich the theory of legal pluralism through locality-based legal harmonization. The findings indicate that the application of Article 108 of the Environmental Protection and Management Act (UUPPLH) remains discriminatory, as most of those prosecuted are indigenous farmers, even though most of the fire hotspots originate from concession areas. This situation is influenced by the ambiguity of the term “local wisdom” and weak inter-agency coordination. The study proposes a Trisubstantial Harmonization Model, which includes strengthening the legal structure, revising legal substance, and fostering a legal culture.